AKUNTABILITAS KINERJA PEMERINTAH DAERAH DALAM PENYELENGGARAAN PELAYANAN PUBLIK DI KABUPATEN LABUHANBATU SELATAN - Wildan Aswan Tanjung; Sampara Lukman; Khasan Effendy; Aries Djaenuri (GoAcademica Research dan Publishing, 2020)
This study illustrates the accountability of local government performance in the administration of public services in South Labuhanbatu Regency which includes honesty and legal accountability, process accountability, and financial accountability and programs. The method used in this research is descriptive research method by conducting surveys and interviews. The study found that licensing is still not focused in one place, licensing procedures that still require manual signatures, internal and external coordination are still manual and the lack of understanding from the community is an obstacle in the performance of public service delivery.